Application of the Nutrition Functional Diversity indicator to assess food system contributions to dietary diversity and sustainable diets of Malawian households. Issue 13 (1st June 2015) - Luckett, Brian G; DeClerck, Fabrice AJ; Fanzo, Jessica; Mundorf, Adrienne R; Rose, Donald
Abstract: Objective: Dietary diversity is associated with nutrient adequacy and positive health outcomes but indicators to measure diversity have focused primarily on consumption, rather than sustainable provisioning of food. The Nutritional Functional Diversity score was developed by ecologists to describe the contribution of biodiversity to sustainable diets. We have employed this tool to estimate the relative contribution of home production and market purchases in providing nutritional diversity to agricultural households in Malawi and examine how food system provisioning varies by time, space and socio-economic conditions. Design: A secondary analysis of nationally representative household consumption data to test the applicability of the Nutritional Functional Diversity score. Setting: The data were collected between 2010 and 2011 across the country of Malawi. Subjects: Households ( n 11 814) from predominantly rural areas of Malawi. Results: Nutritional Functional Diversity varied demographically, geographically and temporally. Nationally, purchased foods contributed more to household nutritional diversity than home produced foods (mean score=17·5 and 7·8, respectively). Households further from roads and population centres had lower overall diversity ( P <0·01) and accessed relatively more of their diversity from home production than households closer to market centres ( P <0·01). Nutritional diversity was lowest during the growing season when farmers plant and tend crops ( P <0·01). Conclusions: The present analysis demonstrates that the Nutritional Functional Diversity score is an effective indicator for identifying populations with low nutritional diversity and the relative roles that markets, agricultural extension and home production play in achieving nutritional diversity. This information may be used by policy makers to plan agricultural and market-based interventions that support sustainable diets and local food systems.